`That time of the month` … for the biggest event of your career! Perception of menstrual cycle on performance of Australian athletes training for the 2020 Olympic and Paralympic Games - McNamara, A.; Harris, R.; Minahan, C. (BMJ Open Sport & Exercise Medicine, 2022)
Objective. This study explored the perceived effect of the menstrual cycle (MC) on the performance of Australian female athletes, preparing for the Tokyo Olympic and/or Paralympic Games.